SHARIA CROWDFUNDING : FUNDING INNOVATION TECHNOLOGY-BASED FOR MSMES - Fitri Setia Okta Ramadhani; Hilda Bakri; Fitri Fitri; Ade Hastuty (Nurul Jadid University, 2025)
Sharia crowdfunding is an innovation in funding that utilizes technology to provide solutions to the problem of limited access to financing for MSMEs by following sharia principles. This study aims to explore the understanding, how it works, and the economic and strategic benefits of sharia crowdfunding in strengthening MSMEs in the sharia economic environment. The method applied in this study is qualitative descriptive with a literature study approach, where data is collected from various sources such as journals, articles, and relevant documents. The findings of the study indicate that sharia crowdfunding applies various sharia contracts such as mudharabah, musyarakah, and qardh hasan which prioritize justice, transparency, and the principle of being free from exploitation. Several platforms such as Ethis and Investree Syariah have shown the success of this model in increasing financial inclusion and empowering MSMEs. However, there are still challenges such as low sharia financial literacy, lack of digital infrastructure, and regulations that are not yet fully mature that need to be resolved. Therefore, there is a need to be cooperative between various parties in terms of education, strengthening regulations, and developing technology to maximize the potential of sharia crowdfunding as a sustainable and inclusive financing solution for MSMEs in Indonesia